ESTIMATION OF EVAPOTRANSPIRATION USING PENMAN-MONTEITH METHOD AND ASTER SATELLITE IMAGES (Study Cases Bandung Area) - NUR (NIM 12803007), ERLIAN
Evapotranspiration is apart of hydrological cycle and one of the most significant component of the hydrologic budget. A number of method for evapotranspiration estimaton have been presented. Most of methods are based on point data wich do not provide a good estimastion of evapotranspiration for large areas. This problem can be solved using remote sensing method that provide evapotranspiration on pixel by pixel basis, then it can be resulted evapotranspiration values spatially. In this research used Penman-Monteith method to estimate evapotranspiraton, some inputs for this method extracted from ASTER (Advanced Spaceborne Thermal Emission And Reflection Radiometric) satellite images. From satellite image processing obtained suface temperature, albedo and emissivity. The data used in this research were meteorological data (air temperature, wind velocity, air humidity, air pressure, sunshine hour) and two ASTER images wich acquired on June 12, 2003 dan October 7, 2005. The result of evapotranspiration estimation on June 12, 2003 range between 1.29-8.72 mm/day and on October 7, 2005 range between antara 2.44-11.4 mm/day. Evapotranspiraton varies according to land cover characteristic. Forest has The highest evapotranspiration values and the lowest values are found in urban, residential area. Land cover changes have significant effect on evapotranspiration.